Stories as property: Narrative ownership as a key concept in victims' experiences with criminal justice. (September 2019) - Pemberton, Antony; Aarten, Pauline GM; Mulder, Eva
This article offers a novel approach to the difficulties experienced by victims in relation to their social surroundings in general, and to justice processes in particular, by expanding on an emerging paradigm of narrative victimology. For victims, ownership of their narrative is a key element of their experience, but this ownership is contested. The article brings together a body of victimological literature drawn from social and personality psychology, criminology and sociology to illuminate mechanisms underlying possible tensions between victims' narratives and other perspectives on their ordeal. These tensions are relevant to understanding secondary victimisation in the criminal justice processes, as well as to understanding the strengths and weaknesses of restorative justice as a possible avenue for meeting victims' needs.